THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF DEVELOPING NATIONAL AESTHETIC WORLDVIEW BASED ON MINIATURE ART (British Journal of Global Ecology and Sustainable Development, 2026)
This article examines the relevance of forming a national and aesthetic worldview based on miniature art. In the context of globalization, the preservation of national cultural heritage and its transmission to younger generations has become increasingly important. The study highlights the need for a scientific understanding of the aesthetic and educational potential of traditional art forms.